Automated rescuing boat tracking system using raspberry pi - Norzeli, Adlan Nafiz; Rasyad, Za’iem Sabielar; Muhammad Razif, Muhammad Rusydi; Misman, Dalila; Mohd Nordin, Ili Najaa Aimi; Shabani, Hikma (2021)
During floods, safety boats will be dispatched to help flood victims. The location tracking system is important to ensure the safety of the victim. Therefore, this project is conducted to track live locations and monitor flood survivors wirelessly. In tracking the victim’s location, a small and compact computer, called a Raspberry Piis installed on the boat and the recorded data has been uploaded online. This will help firefighters to monitor the location of the boat easily and help the victims navigate the boat to a safe place. A safety camera is installed to help firefighters monitor the situation as well. For system validation, various tests are conducted on-road, swimming pool and Panchor river in Muar, Johor, Malaysia. Hence, the performance on road is accurate. In fact, the recorded speed reading is similar to the speed measured by Google Maps. At the Pagoh Higher Education Hub (HPTP), Johor, Malaysia swimming pool, it is observed that, the faster the boat speed, the shorter the time required to complete a 50 meters trip. Finally, the river testing has shown that the boat speed increases when the boat moves in the same direction as the water current and slows down if the boat and river currents move in opposite directions.